Skills for Life. Experience in the University of Guantánamo - Ermelinda Hernández-Fernández; Niursy Bravo-Hernández; Idalmis López-Sánchez (Universidad de Guantánamo, 2017)
In accordance with the present-day ideas this article offers the educators and families information about how to contribute to the young adolescents and children's education so that they live as useful individuals for society. A very important theme for the teaching staff is addressed in the paper, the dialogue Skills for Life Resilience: A glance from the educational perspective, in which basic theoretic and methodological approaches are proposed for a better and exact understanding of the area of educational work carried out by our professionals.